Ritual in sport – an empirical study of table tennis players - Julia Witkowska (Acta Universitatis Lodziensis: Folia Sociologica, 2023)
The article was devoted to analysing the specifics of the phenomenon of rituals and their social impact. Ritual activities can be diverse, and their characteristics are likely to be specific only to certain social groups. The peri-sport sphere is exceptionally saturated with ritual practices, and the interest in this phenomenon may be compounded by the fact that sports are a relatively under-researched area from a social perspective. In analysing aspects related to the practices in question, it was necessary to refer to psychological mechanisms, an anthropological perspective and a key one – the sociological approach of such theorists as Randall Collins, Erving Goffman, and Émile Durkheim.